ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA LINTAS MINAT PADA PEMBELAJARAN BIOLOGI KELAS X IIS SMA NEGERI 11 KOTA JAMBI - Eka sulistiani; Retni S Budiarti; Muswita muswita (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2016)
ABSTRACT. This study aims to determine students' critical thinking skills across an interest in learning biology class X IIS SMA 11 Jambi. The design of this research is descriptive research with quantitative and qualitative research methods. Sources of data in this research is observation sheet, self-assessment questionnaires and assessment questionnaires among students. The results showed the students' critical thinking abilities viewed from 5 critical aspects of forward- thinking that provide a simple explanation of 56.34%, 69.79% Developing basic skills, Summing up 63.66%, 59.69% providing further explanation, set the strategy and tactics 69, 84%. Based on the observation of the students' critical thinking skills that are in the interest of cross criterion was 7.5%, and 92.5% higher. And based on self-assessment questionnaires, critical thinking ability of students is at a low 2.5% criterion, was 37.5%, 32.5% high, very high 27.5%. Based on the assessment questionnaire among students, students' thinking skills are the criteria were 70%, 20%, very high 7.5% and 2.5% lower. This study concluded that the level of critical thinking skills of students cross an interest in learning biology class X IIS SMA 11 Jambi are on average medium and High criteria. Based on this study suggested needs teacher effort in improving students 'critical thinking by using the right strategies that can foster students' critical thinking skills. Keywords: cross interest, critical thinking skills, learning biology.